Performance analysis of cognitive selection mechanism for wireless LAN system - Hashim, Wahidah; Ismail, Ahmad Fadzil; Dzulkifly, Sumayyah; Abd Ghafar, Nadratul (2013)
This paper presents the performance analysis of two proposed cognitive selection mechanisms namely successive and comparative selection for real wireless LAN environments. The objective of this study is to investigate and identify the wireless network characteristics and behavior that will influence the performance of the selection mechanisms among user terminals and access points located in the office area